Description of the musculature of herpailurus yagouaroundi and puma concolor (felidae, carnivora) and myological comparison of the acionychini tribe - Ashtari Mota Piancastelli (2023)
The forelimb of felids has an important role in capturing, subjugating and dispatching prey, as well as in locomotion. For this reason, comparative studies of the forelimb could reflect ecological variables such as prey size preference, habitat, and locomotor mode. However, there are still few studies correlating muscular anatomy with function and ecology in felids. The musculature of the jaguarundi (Herpailurus yagouaroundi) was never described before and there is no published comparison with other members of the tribe Acinonychini, the puma (Puma concolor) and the cheetah (Acinonyx jubatus). The objective of this study is to describe the musculature of the forelimb of the jaguarundi and compare it with the other members of Acinonychini. Both forelimbs of two specimens of jaguarundi and two puma were dissected and documented with digital photos. Muscle attachments were documented with pencil paint directly in the bones. Muscle weight was recorded using a BEL engineering 720g (e:0,01g) precision balance and the musculature data was compared with the puma, the cheetah and other felids as described in the literature. Our results show the m. triceps brachii of the jaguarundi and puma shows five heads, although only four have been described in cheetah. The m. palmaris longus of puma and jaguarundi serves all five digits, while in the ocelot it serves digits II to V. Some fleshy fibers of m. latissimus dorsi insert onto the caudal belly of the m. pectoralis profundus in the jaguarundi and ocelot, which was not documented for the cheetah and puma. The extensor digitorum communis of puma has one more tendon that serves digit I, which was not found in the jaguarundi. However, the pectoralis profundus of puma has a distinct insertion onto supraglenoid tubercle of scapula, which contributes to its stabilization. The presence of five heads of the m. triceps brachii has a role in stabilizing and extending the elbow, which is congruent with terrestrial locomotion. These characteristics suggest that the jaguarundi is more adapted for terrestrial locomotion, although it shows similar proportions of flexor and extensor muscles, a characteristic typical of scansorial locomotion. The presence of five tendons in the m. palmaris longus contributes to the complete closing of the manus, which helps to manipulate prey, and the atypical insertion pectoralis and the extra tendon of extensor digitorum communis of the puma might help its locomotion in rock landscapes.